The larvae of Chinese Hydropsychidae (Insecta: Trichoptera), Part III: Hydromanicus melli Complex, H. canaliculatus, and H. umbonatus - Zhang, Ao; Zhou, Xin (Zootaxa, 2021)
A total of 45 adult and larval specimens of 6 Chinese Hydromanicus species are included in this molecular association analysis. Of these, the larvae of Hydromanicus melli Complex, H. canaliculatus, and H. umbonatus were associated with their adults using independent DNA sequences (the nuclear 28S-D2 fragment and the mitochondrial COI barcode gene) and were compared to metamorphotypes where available. Phylograms based on both genes revealed deep intraspecific divergences in several species, suggesting that cryptic diversity is likely common within the genus. Illustrated larval descriptions are provided for the three associated species. However, the larvae of species in the H. melli Complex cannot be morphologically differentiated from each other.